Use of Resources in the Teaching-learning of Environment Studies - GHOSH, KAVITA (THE PRIMARY TEACHER, 2015)
Teaching just through chalk-and-talk method does not allow the child to explore the world the way it exists and in its entirety. This is particularly true about subjects like Environmental Studies where the essence of the subject lies in hands-on exploration of the surroundings. However, due to multiple reasons, the teaching-learning of this subject many a time gets restricted merely to reading and writing. This paper discusses how resource management is very crucial for a teacher teaching Environmental Studies and how appropriately chosen resources can make learning both meaningful and engaging. One needs to understand that resources can be of several kinds and one need not just restrict to the use of common resources listed in the books. The teacher should know how to locate, procure and use resources in the best interest of her/his learners. The paper is written on suggestive lines and it partly draws from my experience of working with young learners in primary and elementary classes.